2021
DOI: 10.3389/fgene.2021.638236
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Patterns in Blood and Cerebrospinal Fluid of Multiple Sclerosis and Neuro-Behçet Disease

Abstract: Inflammatory demyelinating disorders of the central nervous system are debilitating conditions of the young adult, here we focus on multiple sclerosis (MS) and neuro-Behçet disease (NBD). MS is an autoimmune disorder of the central nervous system. NBD, a neurological manifestation of an idiopathic chronic relapsing multisystem inflammatory disease, the behçet disease. The diagnosis of MS and NBD relies on clinical symptoms, magnetic resonance imaging and laboratory tests. At first onset, clinical and imaging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…We speculate that this IL-10 was not associated with regulatory cells. In line with this observation, a recent report of our team has suggested that this cytokine is elevated in naive treatment NBD patients [ 21 , 43 ]. These data are in accordance with results from Aridogan, et al, who found an increased level of IL-10 in sera of active Behçet’s disease [ 15 ].…”
Section: Discussionsupporting
confidence: 70%
“…We speculate that this IL-10 was not associated with regulatory cells. In line with this observation, a recent report of our team has suggested that this cytokine is elevated in naive treatment NBD patients [ 21 , 43 ]. These data are in accordance with results from Aridogan, et al, who found an increased level of IL-10 in sera of active Behçet’s disease [ 15 ].…”
Section: Discussionsupporting
confidence: 70%
“…A major contribution for IL-10 in controlling MS development has been initially demonstrated in experimental autoimmune encephalomyelitis (EAE) model, a widely used mouse model for MS, where IL-10 knockout mice were shown to develop a more severe disease, whereas IL-10 transgenic mice were completely resistant to disease development [34,35]. In humans, several reports indicated a lower expression of IL-10 in the cerebrospinal fluid and peripheral blood of relapsing MS patients as compared to healthy donors and remitting MS patients [36][37][38] (Fig. 1).…”
Section: Key Pointsmentioning
confidence: 99%